High-internal-phase emulsion loaded with oil-soluble pigment and application of high-internal-phase emulsion in lipstick

By using pea 11S globulin amyloid fibrils as a stabilizer, a high internal phase emulsion loaded with lycopene was prepared, which solved the problem of lycopene degradation in the external environment, improved its stability and antioxidant activity, and was suitable for product development in multiple fields.

CN119792120APending Publication Date: 2025-04-11CHINA AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411770481.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Lycopene is easily oxidized and degraded under the influence of the external environment, affecting its stability and use effect, and is difficult to exert antioxidant activity in products such as lipsticks.

Method used

Pea 11S globulin amyloid fibrils were used as stabilizers to prepare high internal phase emulsions loaded with oil-soluble pigments, and cross-linked β structures and three-dimensional zipper structures were formed through non-covalent interactions, which improved the stability and interface adsorption capacity of the emulsion.

Benefits of technology

A stable high internal phase emulsion was successfully prepared, which improved the stability of lycopene and extended its antioxidant activity. It is suitable for food, cosmetics and health products, and provides moisturizing, antioxidant and anti-inflammatory effects in lipsticks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170142210000101
    Figure BDA0005170142210000101
  • Figure BDA0005170142210000111
    Figure BDA0005170142210000111
  • Figure BDA0005170142210000112
    Figure BDA0005170142210000112
Patent Text Reader

Abstract

The invention provides a high internal phase emulsion loaded with oil-soluble pigment and application thereof in lipstick, which comprises the following steps: preparation of pea 11S globulin amyloid fibril, preparation of lycopene-loaded high internal phase emulsion with stable pea 11S globulin amyloid fibril, preparation of oil-soluble pigment-loaded high internal phase emulsion based on lycopene-loaded high internal phase emulsion, preparation of oil-soluble pigment-loaded high internal phase emulsion based on oil-soluble pigment-loaded high internal phase emulsion, preparation of oil-soluble pigment-loaded high internal phase emulsion based on oil-soluble pigment-loaded high internal phase emulsion, and preparation of oil-soluble pigment-loaded high internal phase emulsion. And adding other ingredients to prepare the edible lipstick. The stable high-internal-phase emulsion is successfully prepared, the lycopene can be protected while being loaded, the stability of the lycopene is improved, and the stable high-internal-phase emulsion can be applied to multiple fields of food, cosmetics, health care products and the like. On the basis of moistening lips and preserving moisture, the lipstick prepared by the invention has the effects of resisting oxidation, resisting inflammation and fading cheilogramma due to the lycopene, and the raw materials are natural edible substances, so that the pursuit of consumers on the health of the lipstick without side effects can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of emulsion preparation, and particularly relates to a high internal phase emulsion loaded with oil-soluble pigments and application thereof in lipstick. Background Art

[0002] Lycopene is an isoprene compound derived from plant foods. It has strong antioxidant activity and can delay aging by scavenging free radicals, enhancing the activity of superoxide dismutase and glutathione peroxidase, and reducing the content of malondialdehyde. It has significant effects in preventing and treating nervous system diseases, inhibiting the proliferation of tumor cells, preventing cardiovascular and cerebrovascular diseases, and preventing and treating osteoporosis. In addition, the antioxidant effect of lycopene can effectively avoid ultraviolet damage caused by long-term sunlight exposure, reduce the damage to deep skin tissues, and reduce wrinkles and freckles. It can be used in functional foods, health products and cosmetics. However, once lycopene is affected by the external environment, it is easy to be oxidized and degraded. The main factors affecting its stability are oxygen, temperature, metal ions, light, acid and antioxidants, which seriously affect its use effect. For example, patent CN202010456618.4 discloses an antioxidant lip balm containing lycopene extract and its preparation method. Its formula is 15-30 parts of isooctyl palmitate, 35-55 parts of cosmetic grade white oil, 25-50 parts of white wax, 1-10 parts of shea butter, 1-20 parts of glycerin, 1-10 parts of vaseline, 1-8 parts of talc, and 0.0001-0.001 parts of lycopene. The prepared lip balm can moisturize the lips, but the added lycopene extract is easily degraded by external factors and cannot exert its antioxidant activity. Therefore, improving the stability of lycopene in the product is of great significance for its application in various fields. High internal phase emulsions (HIPEs) are a type of emulsion with a high oil volume fraction. High concentration emulsion system greater than 74%. Since the volume fraction of the oil phase of the emulsion far exceeds the tight packing limit, the droplets will be highly stacked together and become polygonal under certain conditions. High internal phase emulsions have ideal solid-like texture, high loading capacity, gel rheological behavior and good stability. These characteristics make them uniquely applicable in the fields of food and cosmetics. In general, high internal phase emulsions can be used to load bioactive substances to improve their dispersibility, stability and bioaccessibility. Their good spreadability can be used to replace mayonnaise or fat substitutes in chocolate. In addition, high internal phase emulsions are expected to become a novel and effective alternative to emulsions containing a large amount of surfactants in the preparation of cosmetics. For the specific application of high internal phase emulsions, it is crucial to determine the right stabilizer to enhance their application performance, because as the volume fraction of the internal phase increases, it becomes more challenging to form and stabilize the emulsion. The addition of interfacial stabilizers helps to reduce the interfacial tension of the emulsion to improve the stability of the system. Most stabilizers for high internal phase emulsions use a large number of small molecule surfactants or inorganic particles, but these stabilizers are limited by factors such as cost, safety, and environmental impact and are difficult to apply in the food industry. Therefore, people are currently focusing on stabilizing high internal phase emulsions with protein biomaterials of different dimensions such as nanofibrils and microgels, and have shown good results. Among them, protein amyloid fibrils are highly ordered structures obtained by protein self-assembly, with high aspect ratios, adjustable flexibility, and superior mechanical properties. Compared with natural proteins, they have higher viscosity and gelling properties, which are beneficial to improving the stability of emulsions and are good emulsion stabilizers. Summary of the invention

[0003] Technical problems to be solved: In view of the above technical problems, the purpose of the present invention is to provide a high internal phase emulsion loaded with oil-soluble pigments and its application in lipstick, comprising the following steps: preparation of pea 11S globulin amyloid fibrils, preparation of a high internal phase emulsion loaded with lycopene stabilized by pea 11S globulin amyloid fibrils, and preparation of an edible lipstick based on the high internal phase emulsion loaded with lycopene by adding other ingredients. The present invention successfully prepares a stable high internal phase emulsion, which can provide protection for lycopene while loading lycopene, improves the stability of lycopene, and can be applied to multiple fields such as food, cosmetics, and health products. The lipstick prepared by the present invention has the effects of anti-oxidation, anti-inflammatory, and lightening lip lines because it contains lycopene on the basis of moisturizing lips and moisturizing. The raw materials are all natural edible substances, which can meet consumers' pursuit of healthy lipstick without side effects.

[0004] Technical solution: A high internal phase emulsion loaded with oil-soluble pigments, wherein the high internal phase emulsion uses pea 11S globulin amyloid fibrils as a stabilizer and is obtained by loading the oil-soluble pigments. Furthermore, a method for preparing a high internal phase emulsion loaded with an oil-soluble pigment comprises the following steps: S1. Preparation of pea globulin 11S amyloid fibrils: dissolve pea globulin 11S at a concentration of 10-20 mg / mL in PBS buffer, titrate with HCl solution to a pH of 1-3, centrifuge the solution at 4-25° C. and a centrifugal force of 10000-15000 g for 10-30 min to obtain a supernatant, heat the supernatant at 80-90° C. and stir for 6-12 h, and cool to obtain pea 11S globulin amyloid fibrils; S2. Preparation of a highly stable high internal phase oil-soluble pigment emulsion: pea 11S globulin amyloid fibrils are diluted with PBS buffer to a concentration of 4-8 mg / mL to obtain an aqueous phase, and the oil-soluble pigment is dissolved in edible oil at a ratio of 0.025-0.1wt% to obtain an oil phase, and the aqueous phase and the oil phase are mixed in a mass ratio of 1:(3-6), and the mixture is sheared with a high-speed shearing machine to obtain a highly stable high internal phase oil-soluble pigment emulsion with an oil phase volume fraction of 75-85%. Furthermore, the oil-soluble pigment in step S2 includes lycopene and β-carotene. Furthermore, the edible oil in step S2 includes sunflower oil, soybean oil and algae oil. Furthermore, the high-stability high internal phase oil-soluble pigment emulsion in step S2 has a solid-like texture that does not flow when inverted. Furthermore, in step S2, the shearing speed of the high-speed shearing machine is 6000-10000 rpm, and the shearing time is 1-2 min. The high internal phase emulsion prepared by any of the preparation methods described above is used in the fields of food, cosmetics, and health care products. Furthermore, the cosmetics include edible lipstick. Furthermore, the preparation method of the edible lipstick is as follows: weighing an oil-soluble pigment high internal phase emulsion, natural waxes and natural lipid oil in a mass ratio of (3-5):(1-4):(1-4), stirring and mixing with 1-4wt% of monostearate glyceryl in sequence, heating to 60-80°C to completely melt, then quickly pouring into a lipstick tube that has been disinfected with alcohol while hot, and cooling at room temperature to obtain the edible lipstick. Furthermore, the natural waxes include natural white beeswax and yellow beeswax, and the natural lipid oils include coconut oil, shea butter and olive oil. Beneficial effects: 1. In the present invention, the pea 11S globulin folds after acid-heat treatment, loses its original structure and begins to aggregate, and is interconnected through non-covalent interactions to form oligomers with a cross-linked β structure and a three-dimensional zipper structure. The oligomers are continuously aggregated and superimposed and self-assembled to form fibril aggregates, giving the pea 11S globulin amyloid fibrils the characteristics of a highly ordered structure, a high aspect ratio, and high stability, so that it can be used as a stabilizer for a high internal phase emulsion, improve the adsorption capacity of the emulsion interface, and help improve the stability of the emulsion. 2. The present invention utilizes pea 11S globulin amyloid fibrils to prepare a high internal phase emulsion. When the concentration of pea 11S globulin amyloid fibrils is 4 mg / mL, a near gel structure can be formed, and when the concentration of pea 11S globulin amyloid fibrils is 8 mg / mL, the gel structure formed is the most compact. The present invention can achieve a good high internal phase emulsion gel effect with pea 11S globulin amyloid fibrils of lower concentration, indicating that pea 11S globulin fibrils have a strong ability to stabilize high internal phase emulsions, can save raw materials and reduce costs. 3. The high internal phase emulsion prepared by the present invention can load water-insoluble functional ingredients due to its large dispersed phase volume and gel-like tight structure. The high internal phase emulsion loaded with lycopene can overcome the influence of external environmental factors on its own functional properties. Then, the emulsion was irradiated with ultraviolet light for 6 hours, heated in a water bath at 90°C for 6 hours, and Fe 3+ After 6 hours of treatment, not only the emulsion structure remained intact, but lycopene was also retained to a great extent, indicating that the high internal phase emulsion not only has good stability, but also improves the stability of lycopene, promoting the widespread application of lycopene in the fields of food and life sciences. 4. In the preparation of the lipstick, the lycopene high internal phase emulsion is added instead of directly adding lycopene. The protective effect of the high internal phase emulsion on lycopene is conducive to enhancing the antioxidant and ultraviolet resistance of the lipstick. At the same time, other ingredients are all natural edible substances, all of which are food grade and do not contain chemical components such as heavy metals and mineral oils. The formula is simple and mild, green and environmentally friendly, and each raw material has efficacy, including moisturizing and protecting the skin, etc., which can meet consumers' pursuit of healthy lipstick without side effects. 5. The present invention utilizes pea 11S globulin amyloid fibrils to prepare lycopene high internal phase emulsion, which can significantly improve the comprehensive utilization and development efficiency of lycopene, expand the application scope of protein amyloid fibrils as functional additives, enhance the technical level of production and preparation of high internal phase emulsion, and provide data reference for the application of protein fibrillation in high internal phase emulsion. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 TEM images of pea 11S globulin solutions of different concentrations after heating for different times in Example 1; Figure 2 is the AFM image of pea 11S globulin at different concentrations after forming fibrils in Example 1; Figure 3 is the length and thickness distribution of fibrils formed by different concentrations of pea 11S globulin in Example 1; Figure 4 This is the inversion experiment of high internal phase emulsion stabilized by protein fibrils of different concentrations in Example 2; Figure 5is the variation of the modulus of the high internal phase emulsion stabilized by protein fibrils of different concentrations with strain in Example 2; Figure 6 is the change of the modulus of the high internal phase emulsion stabilized by protein fibrils of different concentrations with frequency in Example 2; Figure 7 is the particle size distribution of the high internal phase emulsion stabilized by protein fibrils of different concentrations in Example 2; Figure 8 It is the microstructure of the high internal phase emulsion stabilized by protein fibrils of different concentrations in Example 2; Fig. 9 This is an inversion experiment of the high internal phase emulsion loaded with different concentrations of lycopene in Example 3; Fig.10 is the variation of the modulus of the high internal phase emulsion loaded with different concentrations of lycopene as a function of strain in Example 3; Fig.11 is the change of the modulus of the high internal phase emulsion loaded with different concentrations of lycopene as a function of frequency in Example 3; Fig.12 is the effect of UV treatment on lycopene in high internal phase emulsions stabilized by protein fibrils at different concentrations in Example 3; Fig.13 is the effect of heat treatment in Example 3 on lycopene in high internal phase emulsions stabilized by protein fibrils at different concentrations; Fig.14 It is Fe in Example 3 3+ Effects of treatment on lycopene in high internal phase emulsions stabilized by different concentrations of protein fibrils; Fig.15 This is a sample picture of the lycopene high internal phase emulsion lipstick in Example 4; Fig.16 is the change of the modulus of the lipstick in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 with strain, wherein Comparative Example 1 is recorded as commercially available lipstick A, Comparative Example 2 is recorded as commercially available lipstick B, and Comparative Example 3 is recorded as commercially available lipstick C; Fig.17 is the hardness of the lipsticks in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3, wherein Comparative Example 1 is recorded as commercially available lipstick A, Comparative Example 2 is recorded as commercially available lipstick B, and Comparative Example 3 is recorded as commercially available lipstick C; Fig.18 is the brittleness of the lipsticks in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3, wherein Comparative Example 1 is recorded as commercially available lipstick A, Comparative Example 2 is recorded as commercially available lipstick B, and Comparative Example 3 is recorded as commercially available lipstick C; Fig.19 It is the viscosity of the lipsticks in Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3, wherein Comparative Example 1 is recorded as commercially available lipstick A, Comparative Example 2 is recorded as commercially available lipstick B, and Comparative Example 3 is recorded as commercially available lipstick C. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 Preparation of 11S amyloid fibrils of vicilin: Pea 11S globulin was dissolved in 10mM phosphate buffer (H3PO4 / NaH2PO4) at pH 2, and protein solutions with concentrations of 10mg / mL, 15mg / mL, and 20mg / mL were prepared. The solution was titrated to pH 2 with 0.1mol / L HCl solution, and the solution was centrifuged at 4°C and 10000×g for 15min to remove insoluble particles to obtain the supernatant. The supernatant was stirred at 300rpm on a heated stirrer at 80°C for 12h. Samples were taken every 6h during the period, and all samples were stored at 4°C for future use. Performance Testing (1) Transmission electron microscope The sample was diluted to 0.2 mg / mL with ultrapure water. A drop of the diluted sample solution was taken and adsorbed on a copper mesh for 1 min. The sample on the copper mesh was then stained with a 2% (w / v) uranyl acetate solution for 30 s and dried naturally. TEM was used to observe the formation of the fiber. Depend on Figure 1 It can be seen that the proteins of different concentrations were mainly distributed in spherical shape at 0h, and no fibers were formed. After heating for 6h, the 10mg / mL protein formed a large number of small aggregates, but no fiber formation was observed; while the 15mg / mL and 20mg / mL proteins formed dense aggregates that were entangled with each other at 6h, and formed large linear clusters through aggregation, accompanied by short fibers around them. Especially under the condition of 20mg / mL protein concentration, it can be observed that obvious fibrils have been formed in the clusters, which shows that the increase in protein concentration accelerates the speed of protein fibril formation. After heating for 12h, it can be observed that proteins of different concentrations can form amyloid fibrils. The low concentration (10mg / mL) protein solution forms a large number of short fibers, and the 15mg / mL and 20mg / mL protein solutions form thick and long rigid fibers. Since the unheated and heated for 6h proteins did not form mature amyloid fibrils, they could not be used as stabilizers for emulsions. The samples heated for 12h were selected for further analysis in subsequent experiments. (2) Atomic force microscopy (AFM) analysis Use tape to remove the burrs on the surface of the mica sheet to reduce the impact on the background. Use ultrapure water to dilute the samples of different protein concentrations (10mg / mL, 15mg / mL, 20mg / mL) after heating for 12 hours to 0.04mg / mL, take a small amount of sample and drop it on a clean mica sheet to dry naturally. Rinse the tray and mica sheet with a small amount of pure water, and test them after drying. Use ScanAsyst mode to output AFM images and count the length and thickness of the fibers. Depend on Figure 2 It can be seen that a large number of short fibers were formed in the low concentration (10 mg / mL) protein solution, and thick and long rigid fibers were formed in the 15 mg / mL and 20 mg / mL protein solutions. This result is consistent with the TEM image obtained previously. Depend on Figure 3 It can be seen that the average length of the fibrils prepared with 10 mg / mL protein solution is 155.76 nm, while the average length of the fibers reaches 664.8 nm and 435.18 nm when the concentration increases to 15 mg / mL and 20 mg / mL, respectively. Therefore, the overall length of the fibrils is the longest when the protein concentration is 15 mg / mL. The height difference between the fiber vertex and the plane is calculated as the fiber diameter. The average diameters of the fibrils formed by 10 mg / mL, 15 mg / mL and 20 mg / mL protein solutions are 3.21 nm, 4.89 nm and 4.65 nm, respectively. Combined with the above analysis of the length and thickness of protein amyloid fibrils, it can be concluded that the average diameter and length of amyloid fibrils prepared by 11S globulin at a concentration of 15 mg / mL are the largest. According to literature reports, the interfacial adsorption capacity of longer fibers is more conducive to emulsion stability. Combined with the purpose of this experiment, the fibrils with the best aspect ratio of 15 mg / mL protein concentration were finally selected as the stabilizer for the subsequent high internal phase emulsion. Example 2 Preparation of high internal phase emulsion using pea 11S globulin amyloid fibrils as stabilizer The screened pea 11S globulin amyloid fibrils with a protein concentration of 15 mg / mL and heated for 12 hours were prepared into fiber solutions with concentrations of 2, 4, 6, 8, and 10 mg / mL using pH 2, 0.01 mol / L PBS buffer as the aqueous phase of the emulsion, and then mixed with sunflower oil in a volume ratio of 1:4. The solutions were dispersed and uniformly sheared at 7000 rpm for 1 min using a high-speed shearing machine to obtain a high internal phase emulsion with an oil phase volume fraction of 80%. Performance Testing (1) Emulsion stability The stability of the emulsion can be preliminarily judged by turning it upside down. If it does not flow after being turned upside down, it means that the emulsion has good stability, otherwise it has weak stability. Depend on Figure 4It can be seen that after the glass bottle containing the emulsion was inverted, the sample liquids with pea 11S globulin amyloid fibril concentrations of 2 mg / mL and 10 mg / mL could not withstand the gravity attraction and flowed down, indicating that a uniform high internal phase emulsion was not formed; while the emulsions formed by pea 11S globulin amyloid fibrils at 4-8 mg / mL did not flow and remained in a nearly solidified state, indicating that the formed emulsions have the ability to resist gravity and have good stability. Therefore, the subsequent experiments used samples with a fiber concentration of 4-8 mg / mL. (2) Rheological properties of emulsions The rheological properties of the high internal phase emulsion were measured using a DHR-2 rheometer. A cone plate with a diameter of 40 mm and an angle of 2° was used to place the high internal phase emulsion between the cone plate and the platform, and the gap height was set to 0.5 mm. After equilibration at 25°C for 3 minutes, a strain scan was first performed at a fixed frequency of 1 Hz, with a strain range of 0.1% to 1000%. Then a frequency scan was performed at a fixed strain of 0.1%, with a frequency scan range of 0.01 to 10 Hz. Depend on Figure 5 It can be seen that in the low strain region, G' and G" remain constant, and the linear viscoelastic region of the high internal phase emulsion is determined (the linear viscoelastic region refers to a linear relationship between the stress and strain of the material within a certain range, that is, the modulus is constant). It can be seen that the storage modulus G' of the emulsion at different fiber concentrations in the linear viscoelastic region is always greater than the loss modulus G", indicating that the emulsion has solid-like viscoelastic behavior, and when the stress increases to a certain level, G" begins to be greater than G', indicating that the high stress destroys the structure of the emulsion and makes it exhibit liquid-like behavior. Figure 6 This reflects that G' has always been dominant in the entire frequency range of 0.01-10 Hz and is greater than G", proving the solid-like characteristics of the high internal phase emulsion, which is consistent with Figure 5 Therefore, the emulsion modulus value is the largest when the concentration of pea 11S globulin amyloid fibrils is 8 mg / mL, indicating that its gel property is the strongest. (3) Emulsion particle size Use a laser particle size analyzer to measure the droplet size of the high internal phase emulsion. Slowly add 200uL of the prepared high internal phase emulsion to the injection port of the particle size analyzer until the light shielding rate reaches 8-15% and then start the measurement. Each sample is scanned three times to take the average value. The refractive index of the sample is 1.476, and the dispersion medium is deionized water with a refractive index of 1.333. Depend on Figure 7 It can be seen that the particle size of each emulsion is unimodal, which is attributed to the uniformity of the high internal phase emulsion. Among them, the emulsion stabilized with 8 mg / mL fiber solution has the smallest particle size of 44.58±1.27 μm, indicating that the droplet size distribution in this system is more concentrated and uniform, and the emulsion is more stable. (4) Emulsion microstructure The microstructure of the emulsion was observed by laser confocal microscopy. First, 0.1 mg / mL Nile red and 0.25 mg / mL Nile blue solutions were prepared with ethanol, and then mixed with sunflower oil and protein amyloid fibril solution at a volume ratio of 1:50 for staining. The dyed fiber solution was mixed with sunflower oil at a volume ratio of 1:4, and fully sheared at 7000 rpm for 1 min to obtain a dyed high internal phase emulsion. The microstructure of the high internal phase emulsion was observed and photographed under a 63x objective lens using an oil immersion lens (100x). Depend on Figure 8 It can be seen that green represents protein fibers stained with Nile blue, and red represents oil droplets stained with Nile red. It can be observed that the oil droplets are wrapped by amyloid fibers. The gaps between the oil droplets in the high internal phase emulsion of pea 11S globulin amyloid fibrils at a concentration of 4 mg / mL are large, and it is impossible to form a honeycomb-like network structure. However, when the concentration of pea 11S globulin amyloid fibrils is 6 mg / mL and 8 mg / mL, the oil droplets of the emulsion are tightly stacked and interconnected, forming an obvious polygonal dense network structure. Among them, the emulsion stabilized by protein fibrils at a concentration of 8 mg / mL has an extremely dense 3D network structure, and the oil droplet size is the most uniform. Therefore, the next step is to select a fiber concentration of 8 mg / mL to prepare a high internal phase emulsion containing lycopene. Example 3 Preparation of high internal phase emulsion containing lycopene: A certain amount of lycopene powder was dispersed in sunflower oil to prepare lycopene oil solutions with mass concentrations of 0.025wt%, 0.05wt%, and 0.1wt%, respectively. A 11S amyloid fiber aqueous solution with a concentration of 8 mg / mL was mixed with the lycopene oil solution in a ratio of 1:4, and dispersed at 7000 rpm for 1 min using a high-speed shearing machine to obtain a high internal phase emulsion loaded with lycopene. Fig. 9 shown. Performance Testing (1) Rheological properties of emulsions The rheological properties of the high internal phase emulsion were measured using a DHR-2 rheometer. A cone plate with a diameter of 40 mm and an angle of 2° was used to place the high internal phase emulsion between the cone plate and the platform, and the gap height was set to 0.5 mm. After equilibration at 25°C for 3 minutes, a strain scan was first performed at a fixed frequency of 1 Hz, with a strain range of 0.1% to 1000%. Then a frequency scan was performed at a fixed strain of 0.1%, with a frequency scan range of 0.01 to 10 Hz. Depend on Fig.10 and Fig.11It can be seen that the addition of lycopene will have a great impact on the gel properties of the high internal phase emulsion. The higher the lycopene concentration, the greater the fluidity of the emulsion, the weaker the gel strength and the lower the stability. When the lycopene concentration is 0.025-0.05wt%, the modulus value of the emulsion remains basically stable, but when the lycopene concentration is 0.1wt%, the modulus value of the emulsion decreases significantly, and it has more liquid properties. (2) Embedding rate Take 0.2mL of the prepared lycopene high internal phase emulsion, add 3mL of anhydrous ethanol and n-hexane mixed solvent (1:2) for extraction, ultrasonicate for 5min at room temperature, centrifuge at 8000rpm for 8min, take 1mL of supernatant and mix with 3mL of n-hexane, and measure the absorbance of the resulting solution at a wavelength of 472nm using a visible spectrophotometer. Calculate the concentration according to the standard curve to obtain the total lycopene content. Take another 0.2mL of the high internal phase emulsion and add 4mL of n-hexane for extraction, vortex for 30s, centrifuge at 3000rpm for 3min, take the supernatant and measure the absorbance under a visible spectrophotometer, calculate the lycopene concentration according to the standard curve, and obtain the free lycopene content. The embedding rate of lycopene in the emulsion is calculated according to the following formula: Embedding rate (%) = (total lycopene content - free lycopene content) / total lycopene content × 100% Table 1 Encapsulation efficiency of lycopene in high internal phase emulsion of Example 3 Lycopene content in oil phase (wt%) Embedding rate (%) 0.025 <![CDATA[91.03±1.92 a ]]> 0.05 <![CDATA[91.32±1.14 a ]]> 0.1 <![CDATA[76.54±0.01 b ]]> Note: There is no significant difference between the same letters in the table (p>0.05), and there is a significant difference between different letters (p<0.05). As shown in Table 1, the lycopene embedding rate of the high internal phase emulsion with a lycopene content of 0.025wt% in the oil phase is 91.03%, and almost all the lycopene is embedded in the oil phase of the emulsion. After further increasing the lycopene concentration to 0.05wt%, the embedding rate of the emulsion reached 91.32%, indicating that the dense structure formed by the emulsion droplets at this concentration can effectively wrap the lycopene. However, when the lycopene content increases to 0.1wt%, the embedding rate decreases significantly, indicating that there is more lycopene on the surface of the dispersed phase in the emulsion. Therefore, 0.05wt% is selected as the most suitable lycopene concentration. (3) Stability evaluation The experimental group was a high internal phase emulsion containing 0.05wt% lycopene, and the control group was an equal amount of lycopene directly dispersed in sunflower oil. The retention rate of lycopene was evaluated by the changes in the retention rate of lycopene under UV treatment, heat treatment and Fe 3+Stability under treatment. The emulsion or oil is placed in a light-proof environment and irradiated with ultraviolet light for 6 hours. Samples are taken every 1.5 hours to measure the retention rate of lycopene in the sample to evaluate the ultraviolet stability. The emulsion or oil is heated in a 90℃ water bath in a light-proof environment for 6 hours. Samples are taken every 1.5 hours to measure the retention rate of lycopene in the sample to evaluate the thermal stability. Take a certain amount of ferric chloride (Fe 3+ The molar ratio of lycopene to protein amyloid fibril was 20:1, and the solution was vortexed until completely dissolved to obtain an aqueous phase. Then, a high internal phase emulsion was prepared according to the emulsion preparation method described in Example 3 for the preparation of a high internal phase emulsion containing lycopene. An equal amount of ferric chloride was added to the control group. 3+ The emulsion or oil was placed at room temperature in a dark environment for 6 hours, and samples were taken every 1.5 hours to determine the retention rate of lycopene in the samples to evaluate the Fe 3+ Stability. The total content of lycopene in each sample was determined according to the total lycopene content determination method described in Example 3 for the embedding rate determination, and the retention rate of lycopene was calculated according to the following formula: Retention rate (%) = lycopene content in samples after sampling at different times / lycopene content in samples at 0h × 100% Depend on Fig.12 It can be seen that after 6 hours of ultraviolet light irradiation, the retention rate of lycopene in the high internal phase emulsions stabilized by protein fibers of different concentrations was above 40%. Among them, the emulsion stabilized by pea 11S globulin amyloid fibrils at a concentration of 8 mg / mL had the best retention rate of lycopene, reaching 66.28%, while the retention rate of lycopene directly dissolved in oil was only 3.73%, indicating that lycopene is easily degraded by ultraviolet light, and the high internal phase emulsion has a good protective effect on lycopene. Depend on Fig.13 It can be seen that after heating at 90°C for 6 hours, the retention rate of lycopene directly dissolved in oil is only 5.04%, and the retention rates of lycopene in emulsions stabilized by pea 11S globulin amyloid fibrils of different concentrations are all above 80%, indicating that only a small amount of lycopene in the emulsion is decomposed due to heat, reflecting the effect of high internal phase emulsions on improving the thermal stability of lycopene. Depend on Fig.14 It can be seen that after 6h of Fe 3+ The lycopene retention rate in the control group dropped sharply and finally reached 17.14%, while the retention rate of lycopene in the emulsion stabilized by pea 11S globulin amyloid fibrils reached more than 60%, especially the retention rate of lycopene in the emulsion at the concentration of 4mg / mL and 8mg / mL pea 11S globulin amyloid fibrils reached 80%. Therefore, the lycopene in the high internal phase emulsion stabilized by pea 11S globulin amyloid fibrils is almost not consumed by iron ions, proving that the emulsion can effectively prevent lycopene from contacting with iron ions and being degraded. In conclusion, the above results indicate that the high internal phase emulsion stabilized by pea 11S globulin amyloid fibrils used in the present invention can effectively load lycopene and improve the sensitivity of lycopene to external environmental factors (ultraviolet light, heat, Fe 3+ )'s resistance and improve its stability. Example 4 Preparation of edible lycopene lipstick stabilized by high internal phase emulsion Take 0.9g natural white beeswax and 0.9g coconut oil, stir and mix, heat to 65℃ and melt, add 0.1g glyceryl monostearate to disperse and dissolve, then add 2.1g lycopene high internal phase emulsion and stir and mix quickly, then pour into the lipstick tube that has been disinfected with alcohol while hot, and cool to room temperature to obtain lycopene edible lipstick. Fig.15 shown. Comparative Example 1 The difference between this comparative example and Example 4 is that a commercially available Uriage small white tube moisturizing lipstick is used, which is recorded as commercially available lipstick A. Comparative Example 2 The difference between this comparative example and Example 4 is that the commercially available Mentholatum Classic Mint Moisturizing Lip Balm was used, which is recorded as commercially available lip balm B. Comparative Example 3 The difference between this comparative example and Example 4 is that a commercially available freezing point color-changing lip balm is used, which is recorded as commercially available lip balm C. Performance Testing (1) Rheological properties A parallel plate with a diameter of 40 mm was selected, and a lipstick of the same size was placed between the parallel plate and the platform, with the gap height set to 4 mm. After equilibration at 25 °C for 2 min, a strain sweep was performed at a fixed frequency of 1 Hz, with a strain range of 0.001% to 10%. Depend on Fig.16 It can be seen that in the linear viscoelastic region (with the increase of strain, G' and G" remain constant), the elastic modulus G' of all samples is greater than the loss modulus G", which reflects the property of the lipstick tending to be solid. There is no significant difference in the modulus value of the homemade lipstick compared with the three commercially available lipsticks, indicating that it conforms to the viscoelastic properties of general lipsticks. Compared with comparative examples 1-3, the linear viscoelastic region of the homemade lipstick is significantly increased, indicating that the homemade lipstick can maintain consistent viscoelastic properties within a larger strain range and has stronger stability. Therefore, the sample lipstick conforms to the properties of general lipsticks on the market in terms of rheological properties and has good stability. (2) Texture analysis The mechanical properties of the lipstick were evaluated by a physical property analyzer. The TA5 probe was used for the test, and the test conditions included: (1) setting the test and target types to "compression" mode and "distance" mode, respectively; (2) the penetration depth was 5 mm; (3) the trigger force was 5 g; and (4) the test speed was 2.0 mm / s. The hardness, brittleness, and viscosity of the lipstick were measured. like Figure 17-19 As shown, the homemade lipstick has a higher hardness, similar to Comparative Examples 1 and 3, and a lower brittleness, similar to Comparative Example 2, indicating that the homemade lipstick is not easy to break, and its texture characteristics are consistent with the properties of general lipsticks on the market. Compared with the three commercially available lipsticks, the homemade lipstick has a higher viscosity, indicating that the lipstick is denser, and thus easier to evenly distribute and stay on the lips. (3) Sensory evaluation 18 subjects aged between 18 and 25 were selected for sensory evaluation. The overall analysis was conducted in a room with natural lighting at room temperature. The subjects scored the samples according to the descriptions given in the sensory standard table (worst is 1 and best is 10), including ten indicators of lipstick appearance, color, smell, hardness, oiliness, touch, spreadability, residue, moisturizing and liking. The sensory scoring criteria are shown in Table 2. The samples were distributed in random order and evaluated anonymously. Table 2 Sensory scoring standards Table 3 Sensory test results of Example 4 and Comparative Examples 1-3 As shown in Table 3, the scores of the lipstick prepared in Example 4 are all higher than those in Comparative Examples 1-3, indicating that the product of the present invention can achieve the same effect as the commercially available lipstick and is sensory acceptable to consumers. The product of the present invention has simpler and milder ingredients, is healthier, and has the characteristics of reducing lip lines. The added lycopene has a good prospect of use as a bioactive substance. The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A high internal phase emulsion loaded with oil-soluble pigments, characterized in that: The high internal phase emulsion is obtained by using pea 11S globulin amyloid fibrils as a stabilizer and loading oil-soluble pigments.

2. The method for preparing a high internal phase emulsion loaded with oil-soluble pigment according to claim 1, characterized in that: The following steps are involved: S1. Preparation of pea globulin 11S amyloid fibrils: dissolve pea globulin 11S at a concentration of 10-20 mg / mL in PBS buffer, titrate with HCl solution to a pH of 1-3, centrifuge the solution at 4-25° C. and a centrifugal force of 10000-15000 g for 10-30 min to obtain a supernatant, heat the supernatant at 80-90° C. and stir for 6-12 h, and cool to obtain pea 11S globulin amyloid fibrils; S2. Preparation of a highly stable high internal phase oil-soluble pigment emulsion: pea 11S globulin amyloid fibrils are diluted with PBS buffer to a concentration of 4-8 mg / mL to obtain an aqueous phase, and the oil-soluble pigment is dissolved in edible oil at a ratio of 0.025-0.1wt% to obtain an oil phase, and the aqueous phase and the oil phase are mixed in a mass ratio of 1:(3-6), and the mixture is sheared with a high-speed shearing machine to obtain a highly stable high internal phase oil-soluble pigment emulsion with an oil phase volume fraction of 75-85%.

3. The method for preparing a high internal phase emulsion loaded with oil-soluble pigment according to claim 2, characterized in that: The oil-soluble pigment in step S2 includes lycopene and β-carotene.

4. The method for preparing a high internal phase emulsion loaded with oil-soluble pigment according to claim 2, characterized in that: The edible oil in step S2 includes sunflower oil, soybean oil and algae oil.

5. The method for preparing a high internal phase emulsion loaded with oil-soluble pigment according to claim 2, characterized in that: The high-stability high-internal-phase oil-soluble pigment emulsion in step S2 has a solid-like texture that does not flow when inverted.

6. The method for preparing a high internal phase emulsion loaded with oil-soluble pigment according to claim 1, characterized in that: In step S2, the shearing speed of the high-speed shearing machine is 6000-10000 rpm, and the shearing time is 1-2 min.

7. Use of the high internal phase emulsion prepared by the preparation method according to claim 1 and any one of claims 2 to 6 in the fields of food, cosmetics and health products.

8. The use according to claim 7, characterized in that: The cosmetic product includes an edible lip balm.

9. The use according to claim 8, characterized in that: The preparation method of the edible lipstick comprises the following steps: weighing an oil-soluble pigment high internal phase emulsion, natural waxes and natural lipid oil in a mass ratio of (3-5):(1-4):(1-4), stirring and mixing with 1-4wt% of glyceryl monostearate in sequence, heating to 60-80°C to completely melt, then quickly pouring the mixture into a lipstick tube that has been disinfected with alcohol while hot, and cooling at room temperature to obtain the edible lipstick.

10. The use according to claim 9, characterized in that: The natural waxes include natural white beeswax and yellow beeswax, and the natural lipid oils include coconut oil, shea butter and olive oil.

Citation Information

Patent Citations

  • Antioxidant lip balm containing lycopene extract and preparation method of antioxidant lip balm

    CN111714413A